A duchess by midnight - Michaels, Charis (Michaels, Charis. Awakened by a kiss, 2022)
"Miss Drewsmina "Drew" Trelayne is a former awkward child and one-time wicked stepsister. Raised by a bitter, overbearing mother, Drew is all grown up and has made peace with her orange hair and bean-pole height. Her transformation has inspired her dream of opening a finishing school that emphasizes inner beauty, capability, and confidence. But launching a school costs money so Drew must begin with private clients who pay well and don't ask many questions. Ian Clayblack, the Duke of Lachlan, lives alone on his Dorset estate, forced by scandal into a smuggler's life. When his estranged sister arrives with her two daughters, he feels obligated to give the girls a proper Season. Venturing back to society could clear his name and provide his vagabond nieces with a better life. Who better to help than the striking Miss Trelayne? Affording Drew's services isn't a problem for Lachlan, but his growing desire for her is. As his nieces warm to her gentle charm, he is overwhelmed by her unique beauty and open manner. When they're caught in a scandalous embrace, nothing short of marriage will save all of them from further scandal. Can a marriage made in haste be love's saving grace?"--Page 4 of cover.